Rapid weight loss followed by recovery time does not affect judo-related performance - Artioli, G. G.; Iglesias, R. T.; Franchini, E.; Gualano, B.; Kashiwagura, D. B.; Solis, M. Y.; Benatti, F. B.; Fuchs, M.; Lancha Jr, A. H. (Journal of Sports Sciences, 2010)
In this study, we investigated the effects of rapid weight loss followed by a 4-h recovery on judo-related performance. Seven weight-cycler athletes were assigned to a weight loss group (5% body weight reduction by self-selected regime) and seven non-weight-cyclers to a control group (no weight reduction). Body composition, performance, glucose, and lactate were assessed before and after weight reduction (5-7 days apart; control group kept weight stable). The weight loss group had 4 h to re-feed and rehydrate after the weigh-in. Food intake was recorded during the weight loss period and recovery after the weigh-in. Performance was evaluated through a specific judo exercise, followed by a 5-min judo combat and by three bouts of the Wingate test. Both groups significantly improved performance after the weight loss period. No interaction effects were observed. The energy and macronutrient intake of the weight loss group were significantly lower than for the control group. The weight loss group consumed large amounts of food and carbohydrate during the 4-h recovery period. No changes were observed in lactate concentration, but a significant decrease in glucose during rest was observed in the weight loss group. In conclusion, rapid weight loss did not affect judo-related performance in experienced weight-cyclers when the athletes had 4 h to recover. These results should not be extrapolated to inexperienced weight-cyclers.